User experiences during the transition to calibration-free sensors with remote monitoring while using automated insulin delivery - a qualitative study - Sehgal, Shekhar; De Bock, Martin; Jones, Shirley; Frewen, Carla; Wheeler, Benjamin J. (Frontiers in Endocrinology, 2023)
To evaluate the experiences of patients with type 1 diabetes following transition from a calibration-requiring to a calibration-free sensor and remote monitoring in the context of using automated insulin delivery (AID).Research Design and Methods: Fifteen participants aged 7-65 years with type 1 diabetes participating in a longitudinal study used a Medtronic® advanced hybrid closed loop (AHCL) device with initially calibration-requiring then calibration-free sensors. Qualitative interviews were conducted ≥20 weeks following use of the calibration-requiring and ≥4 weeks after use of the calibration-free sensors/remote monitoring. Thematic analysis was used to identify key themes and subthemes.Results: At baseline, mean diabetes duration was 14.5 years (±10.9), mean Hba1c 54.8 mmol/mol (±10.2) (7.2±0.9%) and Time in range 75.4% (±11.6). Participants reported a progressive improvement in digital and lifestyle integration, and device trust following transition to calibration-free sensors with remote monitoring potential. They also reported a reduced need for capillary glucose, increased device satisfaction and trust, and reduced burden of diabetes care. Negative aspects reported included periodic early sensor loss, and for some, impaired integration with mobile devices.Transitioning to calibration-free sensors with remote monitoring while using AHCL was associated with better user experience, including perceptions of improved quality of life and a reduced burden of diabetes care. Appropriate expectation setting, training, and ongoing support allow for the optimal user experience while using AHCL.